Diagnostic value of clinical manifestations of Group A and Group B compared with rubella serology results in congenital rubella syndrome - Sulasmi, Sulasmi; Dimiati, Herlina; Andid, Rusdi; Darussalam, Dora; Thaib, Teuku Muhammad; Anidar, Anidar (Indonesian Pediatric Society, 2024)
Background Congenital rubella syndrome (CRS) is the triad of defects/abnormalities in the heart, eyes, and ears, resulting from rubella virus infection, especially in the first trimester of pregnancy. Manifestations of CRS are divided into Group A including: hearing loss, congenital heart disease, cataracts or glaucoma, and pigmentary; Group consisted of purpura, splenomegaly, microcephaly, mental retardation, retinopathy and icteric radiolucent bone disoreder that appears within 24 hours after birth. CRS diagnosis is based on serologic rubella test results. Comprehensive management of CRS is needed to achieve optimal child development. However, not all referral center hospitals in Indonesia have serological rubella examination modalities. Objective To evaluate the diagnostic value of group A and group B clinical manifestations compared to rubella serology results in the diagnosis of CRS. Methods This cross-sectional study used secondary data from medical records of pediatric patients with suspected CRS who meet the criteria for groups A and B aged less than 12 months who had been hospitalized at Dr. Zainoel Abidin Regional General Hospital, Banda Aceh, during the three-year study period (2019-2021) which have complete data were included in the study. The IgM serology results were used as diagnostic comparison that performed at the age of less than 12 months. Results A total of 126 patients met the inclusion criteria. Sixty-five (51.6%) subjects were male, 80 (63.5%) subjects had normal birth weight, and 89 (70.6%) subjects were aged <6 months. The diagnostic sensitivity for groups A, B, as well as A and B clinical manifestations were 100%, 75%, and 100%, respectively. This excellent sensitivity value suggests that the clinical manifestations of groups A and B would be suitable as screening tools because they could “catch” many patients with suspected CRS. Conclusion The clinical manifestations of group A and group B have excellent diagnostic value as a screening tool for CRS.